FACTORS CONTRIBUTING TO CHILD SEXUAL ABUSE BY TEACHERS IN SCHOOLS: A STUDY OF MASVINGO DISTRICT SECONDARY SCHOOLS - Simuforosa, Magwa; Rosemary, Ngara (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
Learners are at risk of sexual abuse by teachers. This study set to explore the perceptions of learners, teachers and educational psychologists on child sexual abuse in schools. The study is informed by Maslows hierarchy of needs. In an attempt to provide acceptable answers to research problem the qualitative phenomenology design was employed and semi-structured interviews were used to collect the data. Purposive sampling was used to select schools and participants in Masvingo district. The schools selected were 4 and participants were 19 Accepted ethical measures were adhered to during the study. Teschers open coding method of data analysis was used to identify themes and categories. The study found out that child sexual abuse in schools is rampant and that teachers are among the perpetrators of this abuse. Child sexual abuse was said to fall into two categories namely; contact or non -contact sexual behaviour. According to the results of the study multiple factors cause teachers to sexually abuse. Some of these factors include abuse of power by teachers, poverty of learners, lust on the part of the teacher, and disregard of law by teacher. Students were said to be contributors of their own sexual abuse through their seductive behaviours and dressing. In light of these findings recommendations are made with regards to the need for how various stakeholders in the school namely; the Ministry of Primary and Secondary Education, Zimbabwe, policy makers, school heads, teachers, parents and learners to thoroughly understand the forms and root causes of child sexual abuse so as to be able to fight this scourge.